Solidification of Self-Emulsifying Drug Delivery Systems as a Novel Approach to the Management of Uncomplicated Malaria - Eun Bin Seo; Lissinda H. du Plessis; Joe M. Viljoen (MDPI AG, 2022)
Malaria affects millions of people annually, especially in third-world countries. The mainstay of treatment is oral anti-malarial drugs and vaccination. An increase in resistant strains of malaria parasites to most of the current anti-malarial drugs adds to the global burden. Moreover, existing and new anti-malarial drugs are hampered by significantly poor aqueous solubility and low permeability, resulting in low oral bioavailability and patient noncompliance. Lipid formulations are commonly used to increase solubility and efficacy and decrease toxicity. The present review discusses the findings from studies focusing on specialised oral lipophilic drug delivery systems, including self-emulsifying drug delivery systems (SEDDSs). SEDDSs facilitate the spontaneous formation of liquid emulsions that effectively solubilise the incorporated drugs into the gastrointestinal tract and thereby improve the absorption of poorly-soluble anti-malaria drugs. However, traditional SEDDSs are normally in liquid dosage forms, which are delivered orally to the site of absorption, and are hampered by poor stability. This paper discusses novel solidification techniques that can easily and economically be up-scaled due to already existing industrial equipment that could be utilised. This method could, furthermore, improve product stability and patient compliance. The possible impact that solid oral SEDDSs can play in the fight against malaria is highlighted.